Low back pain related to anxiety and depression in police officers at a police station in Lima: Dolor lumbar relacionada con la ansiedad y depresión en policías de una comisaria en Lima. - Santiago Bazan, Cristhian (2020)
Introduction. Low back pain is a public health problem which entails some type of functional limitation in the individual, affecting the quality of life of police personnel. Objective. Relate lumbar pain with anxiety and depression in police officers from a police station in Lima. Material and methods. It is a research with a quantitative, descriptive, analytical and correlational cross-sectional approach, with the participation of 110 participants, which was obtained through a probabilistic sample where all participants had the same opportunity to participate, it was carried out at the commissary from Monserrat, a questionnaire survey to measure lumbar pain in police personnel ¨CDLPP¨ was used to measure low back pain, whose reliability was 0.914 crombach alpha and the Zung test to measure anxiety and depression. Results. 75.5% of police officers were found to suffer from lumbar pain. Likewise, a statistically significant relationship was evidenced between anxiety and low back pain (p = 0.028). Likewise, no statistically significant association was found between low back pain and depression (P> 0.05). Conclusion. Low back pain is associated with depression in police officers at a police station in Lima. Likewise, a high percentage of policemen who suffer from low back pain, taking into account that it is a public health problem, which could lead to some type of disability in the future affecting their quality of life.